Effect of work family conflict on teachers’ family stress, work satisfaction and family satisfaction in national schools in jaffna district - Anandasayanan, S.; Raveeswaran, M.; Raveendran, T. (University of Sairam, 2011)
Managing the conflict between work and family role demands is a critical issue, since that has generated substantial interest for both individual and organization in recent decades. Work /Family Conflict have various outcomes to the individual, the family environment, and the work environment. At the same manner most of the individual level outcomes of work- family conflict focus on the physical and mental health of the individual as well as overall wellbeing. The effects of Work Family Conflict have got the attention of many researchers in various occupations. There has been no attempt to study those effects on national school teachers. In this manner, this study aims to investigate the effects of work family conflict on family stress, work satisfaction and family satisfaction of teachers. The present study has been conducted among the sample of selected five schools (with 200 respondents) from Jaffna District. The study revealed that work family conflict has positive impact on family stress and, have negative impact on work satisfaction and family satisfaction.
Keywords: Work-Family conflict; Family-Work conflict; Work satisfaction; Family satisfaction; Family stress